Zgank, Andrej - (:unkn) unknown (My University, 2026)
Andrej Zgank received his Ph.D. from the Faculty of Electrical Engineering and Computer Science University of Maribor, Slovenia, in 2003. He was a senior researcher at the University of Maribor between 2003 and 2008. He is a full professor at the University of Maribor in the field of telecommunications and Head of the Department Institute of Electronics and Telecommunications (IETK). His research interests are in the areas of automatic speech recognition, language resources design, acoustic classification, digital signal processing, advanced telecommunication services and applications design. He is a member of IEEE, ISCA, and SDJT.